Real Time Eye-Tracking Using Web Camera - Chavda, Riddhi; Barve, Madhura; Doshi, Amit; Karani, Ruhina (International Journal of Computer Sciences and Engineering, 2015)
Traditional input devices such as keyboard, mouse and joystick have been around for some while now. With the advancements in the field of Human Computer Interaction, eye tracking or iris tracking is the most promising field. It will fundamentally change the way we interact with computers. The main aim of this project is to develop a low cost application running in an open source environment and a widely used operating system Linux, to replace the traditional computer mouse with the human iris for cursor movement. The target audience majorly consists of handicapped people or people with physical impairment. The system designed aims at detecting the user’s eye movements for navigating the cursor, analyzing the nature and timing of blinks, which in turn is used as an input to the computer as a mouse click. The system consists of a good resolution Logitech C270 HD webcam, as opposed to the otherwise popular infrared cameras available in the market. The existing cameras used for tracking are highly expensive but our system is affordable and easy to use. In the project we have used the Fabian Timm image processing algorithm to achieve iris tracking. With future development, we believe our system has the potential to be used as a fully functional substitute for the mouse pointer.